ANALISIS STRUKTURALISME GENETIK DAN NILAI PENDIDIKAN KARAKTER NOVEL MARYAM KARYA OKKY MADASARI SEBAGAI BAHAN AJAR SASTRA DI SEKOLAH MENENGAH ATAS - Dewi, Laeli Rohmawati; Rohmadi, Muhammad; Suhita, Raheni (Universitas Sebelas Maret, 2020)
This study aims to describe the intrinsic elements of the novel 1) Maryam by Okky Madasari; (2) the author's view of the world; (3) the value of character education in the novel of Maryam; and (4) the relevance of the novel of Maryam as the materials literature in high school. The research of applying qualitative methods with genetic structuralism approach. Data and data sources this research is the archives/documents and informants. Research subject retrieval technique used the purposive sampling. The technique of data collection used the analysis of documents and in-depth interviews. The validity of the data used triangulation theory and sources. Data analysis technique used analysis of the flow. Results of the study are: (1) there is relationship between substance of the novel of Maryam includes themes, characters and characterization, setting, plot, point of view, and value; (2) the author's world view includes the religious view, humanism, and feminism; (3) the story in the novel of Maryam contains 10 values character education includes religious tolerance, hard working, independent, democratic, curiosity, friendly/communicative, social care, and responsibility; (4) the novel Maryam relevant with learning materials of literature in high school especially in KD (3.8) Interpret the author's view on life in the novel is read and Analyze (3.9) and linguistic content of the novel.